Preparing for the next pandemic: predictors and effects of COVID-19 remote learning - Brenner, Bodhi A.; Thompson-Brenner, Heather (Frontiers in Psychology, 2024)
BACKGROUND The COVID-19 pandemic forced school closures and rapid transitions to distance learning, which were widely associated with negative effects on educational attainment and mental health among youth (Betthäuser et al., 2023, Vaznis, 2021). Research is now emerging about the relationship between distance learning and educational outcomes, as well as factors that sped or delayed the return of in-person learning in specific geographic regions. In the state of Massachusetts, in the United States, high schools (9th-12th grade) varied in the length of time that passed before inperson learning was offered. This study investigated (1) what factors were associated with the date at which schools implemented hybrid/in-person learning, and (2) what factors, including time in remote learning, were associated with loss of educational attainment. METHOD The sample included N=267 regional/local high schools. Analyses investigated whether time to hybrid/in-person learning was associated with the percentage of students from low-income households and from minority ethnic/racial groups, local political affiliations and COVID incidence rate in September 2020, and the size of the district. The second set of analyses examined whether the high schools' observed losses in standardized math test scores between 2019 and 2021 were associated with the amount of time This is a provisional file, not the final typeset article students remained in exclusively remote learning, as well as the percentage of students from lowincome households and minority ethnic/racial groups, the COVID cumulative incidence rate in the region by April 2021, and the size of the school district. RESULTS Multiple linear regression analysis examining variance in the date at which hybrid/in-person learning was implemented was most strongly predicted by the size of the school district. Multiple linear regression analysis regression analysis examining variance in the loss of educational attainment was most strongly predicted by the percentage of students from low-income households in the high school. Exploratory analyses comparing charter schools with regional public high schools found that charter schools showed significantly greater loss of educational attainment, contrary to hypotheses. CONCLUSION Additional protections for students from larger school districts, lower-income families, and charter schools are needed in case of future population-level disruptions in education.